Magnetic Circular Dichroism Evidence for an Unusual Electronic Structure of a Tetracarbene-Oxoiron(IV) Complex - Ye, Shengfa; Kupper, Claudia; Meyer, Steffen; Andris, Erik; Navrátil, Rafael; Krahe, Oliver; Mondal, Bhaskar; Atanasov, Mihail; Bill, Eckhard; Roithová, Jana; Meyer, Franc; Neese, Frank (Journal of the American Chemical Society, 2016)
In biology, high valent oxo-iron(IV) species have been shown to be pivotal intermediates for functionalization of C-H bonds in the catalytic cycles of a range of O -activating iron enzymes. This work details an electronic-structure investigation of [Fe (O)(L )(NCMe)] (L = 3,9,14,20-tetraaza-1,6,12,17-tetraazoniapenta-cyclohexacosane-1(23),4,6(26),10,12(25),15,17(24),21-octaene, complex 1) using helium tagging infrared photodissociation (IRPD), absorption, and magnetic circular dichroism (MCD) spectroscopy, coupled with DFT and highly correlated wave function based multireference calculations. The IRPD spectrum of complex 1 reveals the Fe-O stretching vibration at 832 ± 3 cm . By analyzing the Franck-Condon progression, we can determine the same vibration occurring at 616 ± 10 cm in the E(d → d ) excited state. Both values are similar to those measured for [Fe (O)(TMC)(NCMe)] (TMC = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecane). The low-temperature MCD spectra of complex 1 exhibit three pseudo A-term signals around 12 500, 17 000, and 24 300 cm . We can unequivocally assign them to the ligand field transitions of d → d , d → d , and d → d , respectively, through direct calculations of MCD spectra and independent determination of the MCD C-term signs from the corresponding electron donating and accepting orbitals. In comparison with the corresponding transitions observed for [Fe (O) (SR-TPA)(NCMe)] (SR-TPA = tris(3,5-dimethyl-4-methoxypyridyl-2-methy)amine), the excitations within the (FeO) core of complex 1 have similar transition energies, whereas the excitation energy for d → d is significantly higher (∼12 000 cm for [Fe (O)(SR-TPA)(NCMe)] ). Our results thus substantiate that the tetracarbene ligand (L ) of complex 1 does not significantly affect the bonding in the (FeO) unit but strongly destabilizes the d orbital to eventually lift it above d . As a consequence, this unusual electron configuration leads to an unprecedentedly larger quintet-triplet energy separation for complex 1, which largely rules out the possibility that the H atom transfer reaction may take place on the quintet surface and hence quenches two-state reactivity. The resulting mechanistic implications are discussed.